Bimbingan Dan Konseling Berbasis Gender: Rekonstruksi Pendidikan Seks Dalam Menanggulangi Seks Bebas di Kalangan Remaja Putri - Syahril, Muhammad (An - Nisa`, 2014)
Abstract: The phenomenon of free sex that is growing massively among youths especially the female ones as the most victimized community becomes a serious problem to face recently. In fact, sex education is less succesfull because there are still some misconceptions about it concept it self. The presence of gender-based guidance and conseling is a breakthrough in the reconstruction of sex education that is more responsive to the feminist aspects inherent in adolescent girls whit all the specifics. If gender-based guidance and counseling is actually applied proportionally, the phenomenon of free sex can be resolved effectively because of the ample referencesfor a mentor or counselor to see the sourceof the problem because of the openness aspect so that they can provide an alternative solution.